2014
DOI: 10.2217/cer.13.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness research in antineoplastic-induced nausea and vomiting control in children

Abstract: Antineoplastic-induced nausea and vomiting (AINV) is one of the most distressing adverse effects experienced by adult and pediatric patients receiving antineoplastic agents. Despite this, evidence of the efficacy and safety of antiemetic interventions in children is limited, and prevention and treatment approaches vary widely between centers. The purpose of this review is: first, to describe the barriers to comparative antiemetic effectiveness research in AINV control in children; second, to highlight limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In a systematic review and meta‐analysis, weight gain and sedation (78% [95% confidence interval (CI): 63 to 95%] and 48% [95% CI: 35 to 67%], respectively) were commonly associated with the use of olanzapine in children less than 13 years old . Extrapyramidal symptoms (EPS) and electrocardiograph abnormalities were reported less frequently (9% [95% CI: 4 to 21%] and 14% [95% CI: 7 to 26%], respectively).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…In a systematic review and meta‐analysis, weight gain and sedation (78% [95% confidence interval (CI): 63 to 95%] and 48% [95% CI: 35 to 67%], respectively) were commonly associated with the use of olanzapine in children less than 13 years old . Extrapyramidal symptoms (EPS) and electrocardiograph abnormalities were reported less frequently (9% [95% CI: 4 to 21%] and 14% [95% CI: 7 to 26%], respectively).…”
Section: Resultssupporting
confidence: 64%
“…Therefore systematic reviews evaluating the safety of metoclopramide [5] and prochlorperazine [6] were undertaken, and an existing systematic review of the safety of olanzapine [7] in children was considered by the panel. Primary studies reported separately for patients ࣘ18 years of age or the mean or median age pf participants was ࣘ18 years; iii.…”
Section: Evidence Identification and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Although some patients receiving prophylaxis still experience CINV, studies show that administering prophylactic regimens concordant with published guidelines significantly reduces and controls symptoms for patients receiving moderately emetogenic or highly emetogenic chemotherapy (MEC; HEC). [12][13][14] Despite rigorously-developed guidelines and availability of effective medications to prevent and treat CINV in pediatric cancer patients, the prescription of antiemetic medications in this population varies widely. One study found that 78% of sites self-reported a standardized approach to prophylaxis.…”
Section: Introductionmentioning
confidence: 99%